Moodle 3 E-Learning Course Development : Create highly engaging and interactive e-learning courses with Moodle 3, 4th Edition. - Nash, Susan Smith (Packt Publishing, 2018)
Moodle is a learning platform or Course Management System (CMS) that is easy to install and use, but the real challenge is in developing a learning process that leverages its power and maps the learning objectives to content and assessments for an integrated and effective course. Moodle 3.x E-Learning Course Development guides you through ...